LOYALITAS PELANGGAN YANG DIPENGARUHI OLEH KUALITAS PELAYANAN DAN FASILITAS DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING PADA KERETA COMMUTER LINE (Studi pada Commuter line Rute Bogor ke Jakarta Kota) - Rifan Lackman; Syafieq Fahlevi Almassawa (Journal of Research and Publication Innovation, 2025)
This study aims to determine Customer Loyalty Affected by Service Quality and Facilities with Customer Satisfaction as an Intervening Variable on Commuter line Trains (Study on Commuter line Bogor to Jakarta City Route). In this study the authors used quantitative research methods with an associative descriptive approach. The sampling technique used is Accidental Sampling. This study uses the Rao Purba formula with a margin of error of 5% as many as 386 samples. The data obtained was analyzed using the Structural Equation Modeling Partial Least Square (SmartPLS) technique. The results of this quantitative study indicate that of the 7 hypotheses accepted, namely Service Quality has a significant effect on Customer Satisfaction with a path coefficient value of 0.158 and a p-value of 0.010 <0.05. Facilities have a significant effect on Customer Satisfaction with a path coefficient value of 0.302 and a p-value of 0.000 <0.05. Service quality has a significant effect on Customer Loyalty with a path coefficient value of 0.200 and a p-value of 0.005 <0.05. Facilities have a significant effect on Customer Loyalty with a path coefficient value of 0.154 and p-values of 0.036 <0.05. Customer Satisfaction has a significant effect on Customer Loyalty with a path coefficient of 0.246 and a p-value of 0.001 <0.05. Service Quality through Customer Satisfaction is indirectly significant to Customer Loyalty with a path coefficient of 0.039 and a p-value of 0.026 <0.05. Facilities through Customer Satisfaction are indirectly significant to Customer Loyalty with a path coefficient value of 0.074 and a p-value of 0.002 <0.05. Based on the results of the calculation, it is known that the R Square value obtained is 0.145 and 0.194, indicating that Customer Satisfaction (Y) and Customer Loyalty (Z) can be explained by the Service Quality Variables (X1) and Facilities (X2) by 14.5% and 19.4%, the rest is explained by other variables outside the model.